Anti-corrosion coating
A zinc-based coating with enhanced adhesion properties addresses the weakness of existing coatings, enabling lighter vehicles by securing fastening elements and reducing energy consumption.
Patent Information
- Application Number
- JP2024536187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-21
- Filing Date
- 2022-12-20
- Publication Date
- 2025-01-17
AI Technical Summary
Existing anticorrosion coatings for metal parts in the automotive industry fail to provide sufficient adhesion, leading to structural weakness and increased vehicle weight, which affects energy consumption and emission levels.
A powdered mixture of zinc flakes and zinc oxide, combined with a silane binder and organic solvent, is applied to form a coating with a thickness of 5-15 μm, enhancing adhesion and providing anti-corrosion properties.
The coating significantly improves adhesion, allowing for the use of smaller fastening elements, reducing vehicle weight and fuel consumption while maintaining structural integrity.
Smart Images

Figure 2025501081000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to anticorrosive coatings for metal parts having improved properties, in particular improved adhesion properties of the substrate after coating. [Background technology]
[0002] Various anticorrosive coatings are known in the prior art, using active ingredients including, for example, chromium, aluminum, zinc, silane or molybdenum.
[0003] Such coatings are disclosed in the patent literature, for example in CN111893468, CN112280040, WO0238686(A2), EP3040445, CN105524505.
[0004] However, these various coatings have very different surface properties.
[0005] In the automotive sector, the development of electric vehicles is booming. The difficulty for car manufacturers is the increasing weight of the vehicles: a diesel engine weighs about 100 kg, while a standard battery for an electric vehicle weighs 250-500 kg, with a few models weighing more than one ton. The power consumption of a vehicle is correlated with its weight, and for a comparable distance, a heavy vehicle requires more energy than a light one. Therefore, a solution is needed in this sector to reduce the total weight of the vehicle. A possible solution is to reduce the size and weight of the screws and bolts in the vehicle. It can be assessed that in a given vehicle, by replacing all M12 standard size screws and all M12 standard size bolts with M8 standard screws and bolts, the total weight of the vehicle can be reduced by at least 1 kg. However, the use of screws and bolts smaller than the standard size leads to a weakening of the structure due to loss of adhesion in the assembly. This is why this solution is not state of the art.
[0006] Therefore, there is a need for a coating that can be applied over metal substrates to increase the adhesion between the substrates.
[0007] The coating should also provide corrosion protection properties to the metal substrate.
[0008] The coating should also impart a black appearance to the coated metal substrate.
[0009] The object of the present invention is a solution which has many advantages and improved technical features compared to the prior art. Summary of the Invention
[0010] The object of the present invention also relates to the use of a powdery mixture of zinc flakes and zinc oxide (also called "Zn / ZnO powder") for increasing the adhesion coefficient value of anticorrosive coatings, characterized in that the zinc flakes represent 60-99% of the mixture of zinc flakes and zinc oxide, more specifically 70-95% of the mixture of zinc flakes and zinc oxide.
[0011] The object of the present invention is also to provide a liquid compound, preferably a slurry, for anticorrosive coatings, comprising: - 15 to 30% by weight, preferably 22 to 28% by weight, of Zn, - 0.5 to 10% by weight, preferably 8 to 10% by weight, of ZnO, - 5 to 15% by weight, preferably 10 to 11% by weight, of a silane coupling agent, - 25 to 50% by weight, preferably 30 to 40% by weight, of water; - 10 to 30% by weight, preferably 20% by weight, of at least one organic solvent, - optionally with additives, The percentages relate to the total mass of the liquid compound and include a slurry.
[0012] The subject of the present invention is also a compound according to the invention, which is produced by the following successive steps: (a) preparing a silane bonding agent in water; (b) adding the aqueous solution of step (a) to a solvent-containing solution containing Zn / ZnO powder to dissolve the aqueous solution.
[0013] The object of the present invention is also to provide a method for producing a process for the production of a method for the production of a process ... (a) preparing a silane bonding agent in water; (b) adding the aqueous solution of step (a) to a solvent-containing solution containing Zn / ZnO powder to dissolve it.
[0014] The object of the present invention is also an anticorrosive coating comprising the following successive steps: (a1) applying a liquid compound according to the present invention to the substrate; (b1) drying the coated substrate of step (a1); and (c1) firing the coated substrate of step (b1).
[0015] The object of the present invention is therefore an anticorrosive coating comprising the following successive steps: (a1) applying a liquid compound according to the present invention to the substrate; (b1) drying the coated substrate of step (a1); and (c1) relates to a substrate coated with at least one layer of a compound obtainable by a process for protecting a metal substrate against corrosion with an anticorrosive coating, comprising the step of calcining the coated substrate of step (b1).
[0016] An object of the present invention therefore relates to an anticorrosive coating obtained by drying and then calcining a liquid compound according to the invention, characterized in that the thickness of the coating is between 5 μm and 15 μm, preferably 8 μm plus or minus 3 μm.
[0017] The object of the invention may more particularly relate to vehicles comprising an anticorrosive coating according to the invention, in particular on their fastening means such as bolts, screws, clips, settings, clamps, rivets, etc., and to articles requiring such fastening means, such as assembly plates of said vehicles. Indeed, preferably, the application of the coating on an assembly plate makes it possible to increase the adhesion of said plate in contact with another plate, whether or not it is coated with a similar coating, reducing the risk of said coated plate moving relative to the other plate.
[0018] definition "Anti-corrosion coating" in the context of the present invention should be understood as either the process of anti-corrosion coating or the product for anti-corrosion coating, which product is obtained from the process in this context. The purpose of the coating is to improve the corrosion protection of the surface of the treated article. The coating obtained thus reduces the alteration of the treated article by chemical reaction with oxidizing agents.
[0019] By "powdered mixture of zinc flakes and zinc oxide (also called Zn / ZnO powder)" in the context of the present invention is to be understood zinc flake particles enriched with zinc oxide to give a darker shade to the zinc powder and liquid compound.
[0020] In the context of the present invention, "adhesion coefficient", also called "coefficient of friction at the interface", refers to a method of measuring the coefficient of friction between two coated metal plates. The coefficient of friction μ characterizes friction conditions according to T=μF, where T is the translational force in Newtons required to slide one part over another, and F is the pressure in Newtons between the parts (see FIG. 3 for illustration). Thus, for a given pressure F between two parts, the greater the force T required to apply for translation, the greater the coefficient of friction.
[0021] In the fields of automotive and mechanical construction, the coefficient of friction is an important parameter in screwed assemblies, since it relates the applied tightening torque and the resulting strain on the thread. In a threaded system, a too high coefficient of friction leads to under-tightening between the screw and the nut. This phenomenon can be countered by a suitable change in the coefficient of friction with some kind of lubricant on either or both fastening articles. However, too much lubrication can lead to over-tightening and thus to failure of the connection in use.
[0022] In the context of the present invention, the measurement of the coefficient of friction is carried out at the interface between two coated metal plates according to standard EN1090-2 "Execution of steel structures and aluminum structures-Part 2: Technical requirements for steel structures" Appendix G (EN 1090-2:2008(F)-Appendix G). The two coated plates are fixed relative to each other thanks to some fixing articles and are subjected to a pressure F. One of the plates is called the "fixed plate" and the other plate is called the "mobile plate". A translational force T is applied to the mobile plate to observe its movement relative to the fixed plate and then the adhesion coefficient μ between the two plates is calculated (see FIG. 4). A category is then assigned to the surface treatment according to the value of the measured coefficient of friction: category A for μ≧0.50, category B for 0.40≦μ<0.50, category C for 0.30≦μ<0.40 and category D for 0.20≦μ<0.30. By comparison, the coefficient of friction of a steel surface on another steel surface is about 0.20, and the coefficient of friction of a greased steel surface on a greased steel surface is about 0.10. Furthermore, similar standards have been developed in the automotive field, and the object of the present invention is to be able to predict these standards.
[0023] "Silane" in the context of the present invention is understood to be an organic compound that contains at least one silicon atom with at least one Si-C bond. In silane, the bond with silicon atom is generally a Si-O, Si-Si or Si-H bond, more preferably a Si-O bond, in addition to the Si-C bond. Advantageously, silane contains at least one Si-O functional group, preferably at least two Si-O functional groups, more preferably at least three Si-O functional groups.
[0024] "Additives" in the context of the present invention are to be understood as compounds that enable additional technical effects according to the intended use or purpose. Such additives may typically be rheological agents, in particular wetting agents, surfactants, pH adjusters, salts, superplasticizers, thickeners, pigments, colorants or additional antioxidants.
[0025] By "solvent-containing solution" in the context of the present invention is meant to be understood a solvent-based compounded product.
[0026] By "obtainable", in the context of the present invention, it is to be understood that the product resulting from the process of the present invention can also be obtained by one or several other processes.
[0027] If not specified, the percentages are expressed relative to the total mass of the composition (or more generally the product) considered. [Brief description of the drawings]
[0028] [Figure 1] Shown is the state of the art having a first plate 1, a second plate 2 connected together by a standard screw 3, a standard size nut 4A, and a flexible washer 4B. [Diagram 2] Shown are a first plate 5, a second plate 6, both coated with a coating 7 according to the present invention, connected together by an undersized screw 8 and an undersized nut 9A and a flexible washer 9B. [Diagram 3] 1 shows an implementation of the process for measuring the coefficient of friction. The coefficient of friction μ characterizes frictional conditions according to T=μF, where T is the translational force in Newtons required to slide one part over another, and F is the pressure in Newtons between the parts. [Figure 4]It shows an implementation of the process of measuring the coefficient of friction, with a plate 10 called "fixed plate" and a plate 11 called "movable plate". The plates in this implementation of the measuring process can also be called "test specimen". A translational force T is applied to the movable plate 11, the movement relative to the fixed plate 10 is observed, and then the adhesion coefficient μ between the two plates is calculated. The fixed plate 10 and the movable plate 11 are held together by a fixing means 12 (which in any case allows a translation T). [Diagram 5] 1 shows a top view of a steel test specimen made of C45E+N (yield point ≧430 MPa) with an opening 13, which may be 13.5 mm in diameter, corresponding to an M12 fixture according to standard NF EN 20273. The specimen has a length A and a width B. A and B may be equal, for example equal to 100 mm. The specimen may be provided with at least one opening 14 near the edge of the specimen. Preferably, the specimen comprises four openings 14, the diameter of which is smaller than the diameter of the opening 13. Furthermore, the specimen may have an inclination angle, each inclination being made by receding values C and D from the lengths A and B, respectively. C and D may be equal, for example equal to 6 mm. [Figure 6] FIG. 6 is a side view of the steel test piece made of C45E+N (yield point≧430 MPa) shown in FIG. 5, the test piece having a thickness E. [Figure 7] 1 shows the principle of applied forces (tension / compression) on a pair of specimens 15, 16 consisting of a stationary specimen 15 and a mobile specimen 16. Compressive forces F1, F2, called normal compression forces, are applied to the pair perpendicular to the contact zone Z between the two specimens, while a traction or compression force T is applied parallel to the plane of this contact zone Z. A load cell 17 makes it possible to observe and / or record the compression forces F1, F2. In some cases, a support sleeve 18 could be used to hold the two specimens 15, 16. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The use of zinc and zinc oxide powders in the context of the present invention, and in the context of the processes, compositions, coated substrates and coatings of the present invention, has several advantages.
[0030] On the one hand, the coating of the present invention has the inherent property of anticorrosion, which means that it protects the surface to which it is applied from chemical reactions with external oxidizing agents.
[0031] On the other hand, the coating of the present invention has excellent adhesion to the support (also called substrate) while providing an adhesion coefficient of 0.5 or more. For example, the coating of the present invention has an adhesion coefficient of 0.6 or more, 0.7 or more.
[0032] The technical advantage from this adhesive property is therefore the fastening of the assembly and therefore the reduction of the dimensions of the fastening device (e.g. screw / nut set). In an assembly of two parts held together by one or several fastening means, a low adhesion coefficient between the two parts leads to a movement of the assembled parts, which may result, for example, in loosening of the screw or, more seriously, in damage to the fastening system. A high adhesion coefficient between the two assembled parts therefore makes it possible to reduce the need for distortion in the fastening zone to hold the assembly. This increased adhesion between the plates gives the opportunity to reduce the dimensions of the fastening means used while maintaining the mechanical properties of said fastening means and maintaining the necessary stability of the assembly. Thus, in the assembly, the use of smaller size screws and nuts with a comparable class of steel compared to the standard can be considered, for example, M12 size screws replaced by M8 size screws (see figures 1 and 2). In this way, the weight and / or number of fasteners is reduced and, when such fasteners are used in a vehicle, the total weight of the vehicle is reduced. Reducing the weight therefore means reducing fuel consumption, reducing the emissions of greenhouse gases (such as CO2) from the combustion of such fuels, or increasing the speed of the vehicle. However, these classical anticorrosive protection techniques of the automotive industry, such as electrophoresis, produce coatings whose adhesion coefficient is too low. The coating of the present invention makes it possible to overcome this drawback by imparting corrosion resistance and an increased adhesion coefficient to the coated metal substrate.
[0033] Use of powdered zinc to increase adhesion coefficient. The use of the present invention requires a powdered mixture of zinc flakes and zinc oxide (also called "Zn / ZnO powder"), which can be included in a liquid compound for anticorrosive coatings, characterized in that the zinc flakes make up 60-99% of the mixture of zinc flakes and zinc oxide, more specifically 70-95% of the mixture.
[0034] In a particular embodiment, the anticorrosive coating of the use according to the invention is an anticorrosive coating of a substrate. Advantageously, the substrate is a machine part.
[0035] In a particular embodiment, the substrate is a mechanical part, such as an assembly plate, that requires an adhesion coefficient of more than 0.5, preferably 0.6 or more, or 0.7 or more.
[0036] In certain embodiments, the substrate is a metal part that is subject to some friction or is designed to be subject to some friction.
[0037] In a particular embodiment, the substrate is a fastening means, preferably selected from the list consisting of fastening articles such as bolts, screws, clips, settings, clamps, rivets or suspension arms.
[0038] liquid compound One of the objects of the present invention therefore relates to a liquid compound comprising powdered zinc having a particle size of 1 μm to 40 μm for use in formulating liquid compounds for anticorrosive coatings.
[0039] Preferentially, the liquid compound for the anticorrosive coating according to the invention comprises from 22 to 28% by weight of Zn, from 18 to 27% by weight of Zn, from 19 to 26% by weight of Zn, the percentages being relative to the total weight of the compound.
[0040] More preferentially, the liquid compound for the anticorrosive coating according to the invention comprises from 25% to around 4% by weight of Zn, the percentages being relative to the total weight of the compound.
[0041] Preferentially, the liquid compound for the anticorrosive coating according to the invention comprises 6-14% by weight of ZnO, 7-13% by weight of ZnO, 8-12% by weight of ZnO, 9-11% by weight of ZnO, the percentages being relative to the total weight of the compound.
[0042] Preferentially, the liquid compound for the anticorrosive coating according to the invention comprises between 8% and around 3% by weight of ZnO, the percentages being relative to the total weight of the compound.
[0043] In one embodiment, the liquid compound for the anticorrosive coating according to the invention comprises: - 15-30% by weight of Zn, 22-28% by weight of Zn, 18-27% by weight of Zn, 19-26% by weight of Zn, 20-25% by weight of Zn, the percentages being relative to the total weight of the compound; - 0.5-10% by weight ZnO, 1-10% by weight ZnO, 2-10% by weight ZnO, 3-10% by weight ZnO, 4-10% by weight ZnO, 5-10% by weight ZnO, 6-10% by weight ZnO, 7-10% by weight ZnO, 8-10% by weight ZnO, 7-9% by weight ZnO, the percentages being relative to the total weight of the compound.
[0044] Preferentially, the liquid compounds for anticorrosive coatings according to the invention comprise 20-45% by weight of the mixture Zn / ZnO, 23-42% by weight of the mixture Zn / ZnO, 25-40% by weight of the mixture Zn / ZnO, 27-38% by weight of the mixture Zn / ZnO, 29-36% by weight of the mixture Zn / ZnO, the percentages being relative to the total weight of the compound.Preferentially, the liquid compounds for anticorrosive coatings according to the invention comprise 10% to around 3% of silane coupling agent (additive), the percentages being relative to the total weight of the compound.
[0045] Advantageously, the silane bonding agent is gamma-glycidoxypropyltrimethoxysilane or gamma-glycidoxypropyltriethoxysilane.
[0046] In one embodiment, the liquid compound for the anticorrosive coating comprises: (a) preparing the silane bonding agent in water; (b) adding and dissolving the aqueous solution of step (a) into a solvent-containing solution containing a Zn / ZnO powdery mixture of zinc flakes and zinc oxide, preferably in which the zinc flakes account for 60-99% of the mixture of zinc flakes and zinc oxide, more specifically 70-95% of the mixture of zinc flakes and zinc oxide.
[0047] Preferentially, the liquid compound for the anticorrosive coating according to the invention comprises between 31% and around 5% water, where the percentages are relative to the total mass of the compound.
[0048] Preferably, the types of compounds according to the invention are predominantly aqueous. However, they can be enriched with organic solvents, preferably water-soluble organic solvents, which make it possible to increase the solubility of the various components of the aqueous solution.
[0049] Preferentially, the liquid compound for the anticorrosive coating according to the invention comprises from 20% to around 5% of an organic solvent, the percentages being relative to the total mass of the compound.
[0050] In an advantageous embodiment of the invention, the compounds require organic solvents, for example consisting of glycol ethers, in particular monopropylene glycol, diethylene glycol, triethylene glycol and dipropylene glycol.
[0051] The object of the present invention is more particularly to provide a liquid compound for anticorrosive coatings, - 22 to 28% by weight of Zn, - 7 to 9% by weight of ZnO, - 5 to 15% by weight, preferably 10 to 11% by weight, of a silane coupling agent, - 25 to 50% by weight, preferably 26 to 40% by weight, of water; - 10 to 30% by weight, preferably 20% by weight, of at least one organic solvent, - optionally at least one additive, Percentages relate to liquid compounds relative to the total mass of the liquid compound.
[0052] Preferably, the mentioned additives improve the rheological properties, which allows easier compounding of the compound. As non-limiting examples, the additives include: wetting agents, such as alcoholates of fatty alcohols; pH regulators, for example alkali metal oxides or hydroxides, preferably selected from lithium and sodium, the oxides or hydroxides of metals of groups IIA and IIB of the periodic table, for example strontium, calcium, barium, magnesium and zinc, or the carbonates or nitrates of the abovementioned metals, - phosphates, such as aluminum dihydrogen triphosphate; - salts, either organic or inorganic, such as alkali silicates, - surfactants such as acrylic copolymers or ethoxylated alcohols, thickening agents, which may be chosen in particular from cellulose derivatives, in particular hydromethylcellulose, hydroxyethylcellulose, hydroxypropylcellulose, hydroxypropylmethylcellulose, xanthan gum, or associative thickening agents, such as of polyurethane or acrylic type;
[0053] In one embodiment, the composition according to the invention may further comprise 0.5 to 4% by weight of aluminum dihydrogen triphosphate, the percentages being relative to the total weight of the compound.
[0054] Preferably, the composition according to the invention may contain 2% by weight ±1% by weight of aluminum dihydrogen triphosphate, the percentages being relative to the total mass of the compound. Thus, aluminum dihydrogen triphosphate may act as a corrosion inhibitor.
[0055] In one embodiment, the composition according to the invention may contain 0.5 to 4% by weight of a molybdenum salt, in particular molybdenum oxide MoO3, the percentages being relative to the total weight of the compound.
[0056] Preferably, the composition according to the invention may contain 2% by weight ±1% by weight of molybdenum salt, in particular molybdenum oxide MoO3 (in particular incorporated in the compound), the percentages being relative to the total mass of the compound.
[0057] Therefore, molybdenum oxide MoO3 can act as a corrosion inhibitor.
[0058] Liquid Compound Manufacturing Process The object of the present invention is also a process for the preparation of said compound, comprising the following successive steps: (a) preparing a silane bonding agent in water; (b) adding and dissolving the aqueous solution of step (a) into a solvent-containing solution containing a powdered mixture of zinc flakes and zinc oxide (also referred to as "Zn / ZnO" powder), preferably wherein the zinc flakes comprise 60-99% of the mixture of zinc flakes and zinc oxide, more specifically 70-95% of the mixture of zinc flakes and zinc oxide, and
[0059] In one embodiment, the process according to the invention may be characterized in that the powdered zinc has a particle size of 1 μm to 40 μm, 1 μm to 35 μm, 1 μm to 30 μm, 1 μm to 25 μm, 1 μm to 20 μm, 1 μm to 15 μm or 1 μm to 10 μm.
[0060] An object of the present invention therefore relates to a liquid compound for anticorrosive coatings which can be obtained by a manufacturing process as described in the above embodiments.
[0061] Processes to protect metal substrates from corrosion The object of the present invention is also a process for protecting a metal substrate from corrosion by the formation of an anticorrosive coating, comprising the following successive steps: (a1) applying a liquid compound according to the present invention to the substrate; (b1) drying the coated substrate of step (a1); (c1) calcining the coated substrate of step (b1).
[0062] The drying step (b1) can be carried out at a temperature between 60°C and 100°C.
[0063] The firing step (c1) can be carried out at a temperature of 300°C to 350°C.
[0064] Preferably, before step (a1), a cleaning step of the metal substrate can be accomplished, which consists of immersing the metal substrate in a cleaning solution, preferably an alkaline solution, extracting the metal substrate from the cleaning solution, rinsing and drying the metal substrate.
[0065] An object of the present invention therefore relates to a substrate coated with at least one layer of a compound obtainable by the process for protecting metal substrates against corrosion as described above.
[0066] Advantageously, the coated substrate of the invention may be characterized in that the substrate is a machine part, such as an assembly plate, requiring an adhesion coefficient of 0.5 or more, preferably 0.6 or more, or 0.7 or more.
[0067] In certain embodiments, the coated substrate is a fastening means such as a bolt, screw, clip, setting, clamp, rivet, or a fixed article such as a suspension arm.
[0068] Advantageously, the anticorrosive coating according to the invention is applied to part of a fastening means as described above, for example a part designed to be in contact with a fastening means of another part.
[0069] Such a contact may be, for example, the threads of a bolt or a screw.
[0070] Anti-corrosion coating An object of the present invention therefore relates to an anticorrosive coating obtained by drying and then calcining a liquid compound according to the invention, characterized in that the thickness of the coating is between 5 μm and 15 μm, preferably 10 μm plus or minus 3 μm.
[0071] The drying step can be carried out at a temperature between 60°C and 100°C.
[0072] The firing step can be carried out at a temperature of 300°C to 350°C.
[0073] How the invention can be put into practice will now be described, by way of non-limiting example, with reference to the accompanying drawings, in which: EXAMPLES
[0074] Example 1: Formula of "Liquid Compound A" according to the present invention
[0075] [Table 1]
[0076] Example 2: Formula of "Liquid Compound B" according to the prior art
[0077] [Table 2]
[0078] Example 3: Measurement of the friction coefficient at the interface Steel specimens are made of C45 E+N (yield point ≥ 430 MPa). The opening diameter of 13.5 mm corresponds to the M12 fixture according to standard NF EN 20273 (see Figure 5). The minimum preload applied is 42 500 N.
[0079] Three types of test specimens are manufactured (see Figure 5). - a test specimen coated with a solid coating made from liquid compound B, having a thickness of 7-9 μm. Compound B and the process for obtaining solid coating B from liquid compound B are described in table 2 of WO 02 / 38686. - Test specimens coated with a solid coating A made from liquid compound A, having a thickness of 7-9 μm. - Test specimens coated by electrophoresis with a thickness of 15-20 μm.
[0080] The specimens are pressed together with a controlled force and held on a test stand. One of the specimens is stationary while the other is movable. A load is applied to the movable specimen and the coefficient of friction at the interface between the two specimens is measured (see Figure 6).
[0081] The results obtained are shown in the table below.
[0082] [Table 3]
[0083] The results show that configuration 1 has poorer results, with a coefficient of friction at the interface of about 0.064. For reference, the coefficient of friction of uncoated steel against uncoated steel is, according to the literature, about 0.2. Applying a solid coating from the Liquid A or B compound on at least one of the two substrates makes it possible to increase this value beyond 0.4, as shown by configurations 2 to 5.
[0084] The best results are obtained for a system having a movable specimen coated with a solid coating from Liquid Compound A associated with a fixed specimen coated with a solid coating from Liquid Compound A.
[0085] These results indicate that the use of a solid coating according to the present invention on an assembly article can result in a system with a high coefficient of friction.
Claims
1. 1. Use of a powdered mixture of zinc flakes and zinc oxide Zn / ZnO for increasing the adhesion coefficient value of an anticorrosive coating, characterized in that said zinc flakes represent 60-99% of said mixture of zinc flakes and zinc oxide, more particularly 70-95% of said mixture of zinc flakes and zinc oxide.
2. A liquid compound for anticorrosive coatings, comprising: - 15 to 30% by weight of Zn, - 0.5 to 10% by weight of ZnO, - 5 to 15% by weight of a silane coupling agent, - 25 to 50% by weight of water, - 10 to 30% by weight of at least one organic solvent, - optionally containing additives, A liquid compound, the percentages being relative to the total mass of said liquid compound.
3. The composition according to claim 2, further comprising 0.5 to 4% by weight of aluminum dihydrogen triphosphate relative to the total weight of the compounds.
4. A process for producing a compound according to claim 2 or 3, comprising the following successive steps: (a) preparing a silane bonding agent in water; (b) adding and dissolving the aqueous solution of step (a) into a solvent-containing solution containing a powdered mixture of zinc flakes and zinc oxide Zn / ZnO, preferably wherein the zinc flakes constitute 60-99% of the mixture of zinc flakes and zinc oxide, more specifically 70-95% of the mixture of zinc flakes and zinc oxide.
5. 5. The process according to claim 4, characterized in that the powdered zinc has a particle size of 1 μm to 40 μm.
6. 1. A process for protecting a metal substrate from corrosion with an anticorrosive coating comprising the following successive steps: (a1) applying to the substrate a liquid compound according to claim 2 or 3; (b1) drying the coated substrate of step (a1); (c1) calcining the coated substrate of step (b1).
7. A substrate coated with at least one layer of a compound obtainable from the process according to claim 6.
8. 8. Substrate according to claim 7, characterized in that the substrate is a fastening means, preferably selected from the list consisting of fastening articles such as bolts, screws, clips, settings, clamps, rivets or suspension arms.
9. An anticorrosion coating obtainable by drying and then calcining a liquid compound according to claim 2 or 3, characterized in that the thickness of said coating is between 5 μm and 15 μm, preferably 8 μm plus or minus 3 μm.
Citation Information
Patent Citations
Corrosion-resistant coating composition
JP1982057758A
Rustproof coated article and coating film forming method
JP2006187679A
Lithographic printing plate master, method for producing lithographic printing plate, lithographic printing method, and curable composition
WO2020045587A1